2018
DOI: 10.1002/gcc.22529
|View full text |Cite
|
Sign up to set email alerts
|

NKX6.1 hypermethylation predicts the outcome of stage II colorectal cancer patients undergoing chemotherapy

Abstract: Colorectal cancer (CRC) is a common malignancy worldwide. CRC patients in the same stage often present with dramatically different clinical scenarios. Thus, robust prognostic biomarkers are urgently needed to guide therapies and improve treatment outcomes. The NKX6.1 gene has been identified as a hypermethylation marker in cervical cancer, functioning as a metastasis suppressor by regulating epithelial-mesenchymal transition. Here, we investigated whether hypermethylation of NKX6.1 might be a prognostic biomar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 55 publications
0
23
0
Order By: Relevance
“…In addition to our reports, the differential methylation of NKX6.1 has also been observed in various types of cancer including B-cell lymphoma [ 24 ], acute lymphoblastic leukemia [ 25 ], astrocytoma [ 26 ] and gastric cancer [ 27 , 28 ]. Moreover, we recently demonstrated that NKX6.1 methylation was an independent indicator of 5-year disease-free survival in stage II CRC patients receiving adjuvant chemotherapy [ 29 , 30 ]. Our findings suggested that NKX6.1 hypermethylation is related to the chemotherapy response and has medical potential in optimizing the selection of therapy.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to our reports, the differential methylation of NKX6.1 has also been observed in various types of cancer including B-cell lymphoma [ 24 ], acute lymphoblastic leukemia [ 25 ], astrocytoma [ 26 ] and gastric cancer [ 27 , 28 ]. Moreover, we recently demonstrated that NKX6.1 methylation was an independent indicator of 5-year disease-free survival in stage II CRC patients receiving adjuvant chemotherapy [ 29 , 30 ]. Our findings suggested that NKX6.1 hypermethylation is related to the chemotherapy response and has medical potential in optimizing the selection of therapy.…”
Section: Introductionmentioning
confidence: 99%
“…A retrospective clinical analysis reports better chemotherapy treatment response in Nm23-expressing tumors [202]. A recent study links a higher promoter methylation status of the metastasis suppressor NK6 homeobox 1 (NKX6.1) resulting in reduced expression, with a less favorable prognosis of stage II CRC patients after receiving adjuvant chemotherapy [203]. This points to a promising strategy to re-express MSGs in cancer cells.…”
Section: Metastasis Suppressors-natural Borne Inhibitorsmentioning
confidence: 99%
“…The vast majority of genes that are found to be hypermethylated are associated with a worse response to therapy. CRC patients with hypermethylated NKX6.1 , TFAP2E , IGFBP3 , and HYAL2 genes did not profit from 5-FU-based chemotherapy [ 173 , 174 , 175 , 176 ].…”
Section: Clinical Applications Of Dna Methylation Profilingmentioning
confidence: 99%